Cytomegalovirus infection after liver transplantation incidence, risks, and benefits of prophylaxis - Weigand, Kilian; Schnitzler, Paul; Schmidt, Jan; Chahoud, Fadi; Gotthardt, Daniel; Schemmer, Peter; Stremmel, Wolfgang; Sauer, Peter (Transplantation proceedings, 2010)
Cytomegalovirus (CMV) infection and related disease is a feared complication after liver transplantation. Antiviral prophylaxis is recommended in clinical practice guidelines depending on the CMV status of both donor and recipient as well as the individual risk profile.